Nicotine kiss : an Amos Walker novel - Estleman, Loren D. (Estleman, Loren D. Amos Walker novels., 2006)
Sometimes friendship is the only thing you can count on. Just before Thanksgiving, an old friend, cigarette smuggler Jeff Starzek, saved private detective Amos Walker's life by getting him to the hospital when he was shot. After New Year's, Walker gets a frantic call from Starzek's sister. Jeff's missing; hasn't been in touch for weeks. It's just not like him. Now Walker, still gimpy and rehabbing, is trying to find Starzek. All he has to go on is his knowledge of Starzek's territory<U+2014>the Lake Huron shore north of Detroit<U+2014>and a tip from Homeland Security agent Herbert Clemson. Clemson, who is also looking for Starzek, says the missing man might be connected to counterfeiters with ties to terrorists. Walker can't really see Starzek getting involved in a scheme so different from his usual line of work. When he visits the man's brother, a minister of an evangelical church, Walker finds a huge stack of treasury paper perfect for printing $20 bills<U+2014>but Starzek's brother is also missing. The counterfeiters are damn serious<U+2014>serious enough to make Starzek's brother disappear, and serious enough to try and kill Walker when he pokes around their operation. Hell of a way to protect an investment. But Walker, gimpy, in pain, cold and tired, can't give up on Starzek. It's a matter of friendship, and he won't let down a friend. He just hopes his loyalty doesn't get him killed.